Hot Press Method: Toward an All‐Ceramic Cathode–Electrolyte Interface with Low‐Temperature Pressed NASICON Li1.5Al0.5Ge1.5(PO4)3 Electrolyte (Adv. Mater. Interfaces 12/2020). Issue 12 (23rd June 2020) - Paolella, Andrea; Zhu, Wen; Bertoni, Giovanni; Perea, Alexis; Demers, Hendrix; Savoie, Sylvio; Girard, Gabriel; Delaporte, Nicolas; Guerfi, Abdelbast; Rumpel, Matthias; Lorrmann, Henning; Demopoulos, George P.; et al.
Abstract : In article number 2000164, Andrea Paolella, Karim Zaghib, and co‐workers describe a new hot press method to densify NASICON Li1.5 Al0.5 Ge1.5 (PO4 )3 (LAGP) with high ionic conductivities at only 650 °C by applying pressure (56 MPa). The cover shows the possible applications of an all solid‐state battery based on a LiFePO4 olivine cathode, LAGP electrolyte and lithium metal.